1999
DOI: 10.1002/(sici)1521-4079(199908)34:7<873::aid-crat873>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Studies of Gel Grown Ferroelectric RbHC4H4O6 and SrC4H4O6 4H2O Crystals

Abstract: Cryst. Res. Technol. 341999 7 873-880Single crystals of Rubidium Hydrogen Tartrate (RbHT) and Strontium Tartrate Tetrahydrate (SrTT) have been grown by a gel technique using a chemical reaction method. A controlled reaction has been employed between tartaric acid and feed solution (RbCl for RbHT and Sr(NO 3 ) 2 ) at room temperature. The laser Raman and FT-IR spectra of these crystals are recorded in the frequency range 100 -4000 cm -1 . The presence of tartrate ion, monohydrogen tartrate ion, water molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Nonlinear optical devices based on second harmonic generation, crystal oscillators and rescuators, and devices to central laser emission are some of these applications. It has also been identified as a strategic material with a global business potential (Selvasekarapandian et al 1999). TGA and DTA studies on STT (Rahimkutty et al 2001) have concluded that water molecules are locked up with different strengths in the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optical devices based on second harmonic generation, crystal oscillators and rescuators, and devices to central laser emission are some of these applications. It has also been identified as a strategic material with a global business potential (Selvasekarapandian et al 1999). TGA and DTA studies on STT (Rahimkutty et al 2001) have concluded that water molecules are locked up with different strengths in the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these potential characteristics tartrate crystals are exploited for their use in transducers and in several linear and nonlinear mechanical devices. They are also used in nonlinear optical devices, optical transmission characteristics, fabrication of crystal oscillators and controlled laser emission [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Tartrate single crystals find application in non-linear optical devices because of their optical second harmonic generation, optical transmission characteristics, fabrication of crystal oscillators and resonators and controlled laser emission [4][5][6][7][8][9]. Strontium tartrate exhibits pyroelectric and ferroelectric transitions [10], non-linear optical and spectral characteristics [11] and dielectric and optical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR analysis of strontium and rubidium tartrates [12] and the dielectric behaviour of calcium [14], sodium-ammonium [15] and zinc [16] tartrates were studied and reported.…”
Section: Introductionmentioning
confidence: 99%